Quantifying mechanical loading and elastic strain energy of the human Achilles tendon during walking and running - Mohamadreza Kharazi (Nature Portfolio, 2021)
Abstract The purpose of the current study was to assess in vivo Achilles tendon (AT) mechanical loading and strain energy during locomotion. We measured AT length considering its curve-path shape. Eleven participants walked at 1.4 m/s and ran at 2.5 m/s and 3.5 m/s on a treadmill. The AT length was defined as the distance between its origin at the gastrocnemius medialis myotendinous junction (MTJ) and the calcaneal insertion. The MTJ was tracked using ultrasonography and projected to the reconstructed skin surface to account for its misalignment. Skin-to-bone displacements were assessed during a passive rotation (5°/s) of the ankle joint. Force and strain energy of the AT during locomotion were calculated by fitting a quadratic function to the experimentally measured tendon force–length curve obtained from maximum voluntary isometric contractions. The maximum AT strain and force were affected by speed (p < 0.05, ranging from 4.0 to 4.9% strain and 1.989 to 2.556 kN), yet insufficient in magnitude to be considered as an effective stimulus for tendon adaptation. Besides the important tendon energy recoil during the propulsion phase (7.8 to 11.3 J), we found a recoil of elastic strain energy at the beginning of the stance phase of running (70–77 ms after touch down) between 1.7 ± 0.6 and 1.9 ± 1.1 J, which might be functionally relevant for running efficiency.